1998
DOI: 10.1136/bmj.316.7147.1776
|View full text |Cite
|
Sign up to set email alerts
|

Screening for chlamydial infections and the risk of ectopic pregnancy in a county in Sweden: ecological analysis

Abstract: Objectives: To analyse trends in rates of genital chlamydial infection and ectopic pregnancy between 1985 and 1995 in a county in Sweden. Setting: Uppsala county where screening for chlamydial infection, treatment, and contact tracing has been widespread and where ectopic pregnancies are recorded. Methods: Rates of chlamydial infections and ectopic pregnancy between 1985 and 1995 were calculated for women aged 20-39 years. Poisson and linear regression were used to examine the association between the risk of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
7

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(107 citation statements)
references
References 24 publications
2
98
0
7
Order By: Relevance
“…The incidence of pelvic inflammatory disease and its sequelae has fallen markedly in countries like Sweden and parts of the USA where there are screening programmes for chlamydia. More recently, Egger et al [98] have shown that the rate of ectopic pregnancy reduced in the first year after the introduction of screening.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pelvic inflammatory disease and its sequelae has fallen markedly in countries like Sweden and parts of the USA where there are screening programmes for chlamydia. More recently, Egger et al [98] have shown that the rate of ectopic pregnancy reduced in the first year after the introduction of screening.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of genital chlamydia began to decrease during the late 1980s, in association with the implementation of routine screening of women, increased screening among men, contact tracing and the establishment of youth clinics (16,(26)(27)(28)(29). The number of reported cases dropped from approximately 40,000 cases in 1987 to 14,000 cases in 1996, which has been accompanied by a corresponding reduction in the number of cases of PID and ectopic pregnancy (29-31).…”
Section: Methodsmentioning
confidence: 99%
“…Integrated STI surveillance, together with screening guidelines for C. trachomatis, have been shown to reduce the incidence of infection and its sequelae. 19,20 Given the serious sequelae of C. trachomatis infections, 15 the probable under-diagnosis and under-reporting of disease, and the high rates of infection reported here, developing a national strategy for the management of STIs which incorporates screening and treatment guidelines for C. trachomatis and N. gonorrhoeae, as well as integrated national clinic and laboratory-based surveillance, should be considered a public health priority in New Zealand.…”
Section: Discussionmentioning
confidence: 99%